A Study on Training Needs of Animal Husbandry Practices in Banda District of U.P. (Indian Journal of Extension Education, 2017)
The present study was conducted purposively in Banda district of Uttar Pradesh as these districts have a sizeable proportion of livestock farmers. Sixteen villages namely Padmai, Nauhai, Tindwara, Marka, Turra, Sikahula, Barcha, Padmai, Musivan, Jamun, Oran, Palhari, Karhuli, Mahokar, Para and Chhapar were selected randomly from district for the present study. From each village ten interested framers were selected randomly. Total 160 interested livestock owners were selected on the basis of Random Proportionate Sampling (RPS) method. The results were calculated as weighted score for each of the thrust area identified (feeding, management, breeding and health care practices) for the training. The findings of the study revealed that ’management practices’ was the most important area and ranked first by the respondents for the purpose of training (mean weighted score 2.138) followed by the area of ’health care (2.103), breeding practices (2.095), and ’feeding practices’ (mean weighted score 2.066), respectively. Therefore realistic planning for education and training need to be done to enhance the knowledge level of livestock farmers. Simultaneously, it can also be suggested that the livestock owners should be acquainted with improved A.H. practices in general with respect to management and health care practices in particular through appropriate extension programmes (training, awareness campaign, exhibitions, demonstration etc) to obtain more output from their livestock.